Hand Soap Activity Against the Number oOf Bacterial Colonies from the Housewife's Hand Swab Samples in a Temporary Landfill in Kelurahan Gadang Banjarmasin - Farida Heriyani; Lia Yulia Budiarti; Widya Nursantari; Ayu Apriliani (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: Unhygienic waste handling in a temporary landfill, can make the surrounding environment a source of transmission of pathogenic bacteria and colonization of bacterial growth in the hands. The study aims to identify the type of bacteria on the hands and test the activity of hand wash soap in lowering the number of colonies of hand bacteria. The identification of bacteria against 30 hand swab samples derived from the hands of housewives in temporary landfill (TPS) in Kelurahan Gadang Banjarmasin, was carried out in conventional media. Test the activity of hand wash soap in lowering the number of colonies of hand bacteria using 2 different brands. Bacterial identification is carried out by descriptive method and experimental testing of hand wash soa p activity use pretest-posttest design with control group design. The data was analyzed using shapiro wilk test and wilcoxon test with 95% confidence level. Identification of hand swab bacterial isolates obtained Staphylococcus aureus (66.6%), Staphylococcus epidermidis (10%) and Escherichia coli (23.33%). Statistical analysis showed significant differences between the two brands of hand wash soap tested (sig. 0.000 >0.05). The conclusion of the type of gram-positive bacteria more widely found in the hands of housewives; Type B hand soap has a higher effectiveness in reducing the number of bacterial colonies on the hands than A-brand. Keywords: hand wash soap, housewife hand swab, number of colonies of hand bacteria.